EXPLORATION OF FUNGICIDES AGAINST STEMPHYLIUM BLIGHT OF GARLIC (Journal of Plant Disease Sciences, 2017)
Field experiment was conducted for the management of stemphylium  blight incited by of garlic during 2012-14. Stemphylium vesicarium Rabi Among seven fungicides evaluated under field conditions on the basis of  pooled data Foliar sprays of Tebuconazole @ 0.1% was found significantly  superior to minimize the leaf blight of garlic (PDI 1.90%) which was at par  with Azoxystrobin @ 0.1% PDI 2.74%. The maximum percent disease  control (PDC) was recorded with four sprays at ten days interval initiated at  the onset of disease. Tebuconazole @ 0.1% (89.29%) followed by  Azoxystrobin @ 0.1% (84.55%). Four foliar sprays of Tebuconazole @  0.1% recorded significantly superior yield (168.82 q/ha) which was at par  with Azoxystrobin @ 0.1% (164.60 q/ha).
Keywords: Garlic, Stemphylium blight, fungicides